Acquired Angioedema as the First Sign of Lymphoproliferative Disorder: Case Report and Review of Literature - Juan Carlos Cardenas Rosales; Ahmad Ridwan; Carlos Ruiz-Orasma; Santiago F. Galeano-Lovera; Fernando Gil Lopez; Jhonny Perusina; Jacqueline D. Squire; Liuyan Jiang; Muhamad Alhaj Moustafa; Dana M. Harris; Salma Iftikhar; Bala Munipalli (Journal of Primary Care & Community Health, 2025)
Acquired angioedema due to C1-inhibitor deficiency (AAE-C1INH) is a rare condition characterized by the localized swelling of the deeper skin layers and mucous membranes, especially the face, lips, tongue, throat, and gastrointestinal tract. AAE-C1INH is strongly associated with lymphoproliferative disorders, although it can also be linked to autoimmune conditions, solid tumors, infections, or even occur without an identifiable cause. We present the case of a 45-year-old female patient with complaints of recurrent abdominal pain, bloating, and joint swelling. Laboratory testing showed decreased C1q and C4 complement levels, and C1 esterase inhibitor levels, indicative of AAE-C1INH. Further work up confirmed a diagnosis of extranodal marginal zone lymphoma with involvement of the bone marrow and spleen. Treatment with rituximab led to resolution of angioedema symptoms and almost complete remission of underlying lymphoma. This case underscores the importance of evaluating an underlying lymphoproliferative disorder in AAE-C1INH. Therefore, the early participation of a multidisciplinary team including specialists in immunology, hematology, and oncology is necessary for appropriate management.